Neutron Activated 153Sm Sealed in Carbon Nanocapsules for in Vivo Imaging and Tumor Radiotherapy - Wang, Julie T-W; Klippstein, Rebecca; Martincic, Markus; Pach, Elzbieta; Feldman, Robert; Šefl, Martin; Michel, Yves; Asker, Daniel; Sosabowski, Jane K; Kalbac, Martin; Da Ros, Tatiana; Ménard-Moyon, Cécilia; et al. (ACS nano, 2020)
Radiation therapy along with chemotherapy and surgery remain the main cancer treatments. Radiotherapy can be applied to patients externally (external beam radiotherapy) or internally (brachytherapy and radioisotope therapy). Previously, nanoencapsulation of radioactive crystals within carbon nanotubes, followed by end-closing, resulted in the formation of nanocapsules that allowed ultrasensitive imaging in healthy mice. Herein we report on the preparation of nanocapsules initially sealing "cold" isotopically enriched samarium (152Sm), which can then be activated on demand to their "hot" radioactive form (153Sm) by neutron irradiation. The use of "cold" isotopes avoids the need for radioactive facilities during the preparation of the nanocapsules, reduces radiation exposure to personnel, prevents the generation of nuclear waste, and evades the time constraints imposed by the decay of radionuclides. A very high specific radioactivity is achieved by neutron irradiation (up to 11.37 GBq/mg), making the "hot" nanocapsules useful not only for in vivo imaging but also therapeutically effective against lung cancer metastases after intravenous injection. The high in vivo stability of the radioactive payload, selective toxicity to cancerous tissues, and the elegant preparation method offer a paradigm for application of nanomaterials in radiotherapy.
Keywords: nádory plic; nanokapsle; Lung Neoplasms; povrchové vlastnosti; samarium; Female; Neutrons; nanoencapsulation; neutrony; zvířata; myši; myši inbrední C57BL; velikost částic; Mice; filled carbon nanotubes; Samarium; Carbon; ženské pohlaví; Nanocapsules; Mice, Inbred C57BL; cancer therapy; nuclear imaging; nanooncology; Animals; uhlík; Particle Size; Surface Properties; radiooncology